Analisis Penerapan Aplikasi Sistem Keuangan Desa (SISKEUDES) Versi 2.0.3 Dalam Meningkatkan Kualitas Akuntabilitas Keuangan Desa Pada Masa Pandemi Covid-19 (Studi Pada Desa Kalibukbuk, Kec. Buleleng, Bali) - Asih, Ginanthi; Adiputra, I Made Pradana (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2022)
This research aimed at knowing the application of the SISKEUDES application version 2.0.3 in improving the quality of village financial accountability during the Covid-19 pandemic in Kalibukbuk Village. This study uses a qualitative research approach. The data used are primary data through observation and interviews and secondary data. The informants in this study were the Village Secretary and the Kalibukbuk Village Treasurer. The analytical method used is data collection, data reduction, data presentation, and drawing conclusions. The results show that (1) the implementation of SISKEUDES version 2.0.3 has been carried out in a structured manner. (2) The accountability quality of SISKEUDES version 2.0.3 can improve village financial accountability and produce transparent and accountable financial reports. (3) The positive impact of SISKEUDES on the performance of the village government is felt directly by village officials in Kalibukbuk Village.Â